The Influence of NCT 127 as a Brand Ambassador and Brand Trust on Consumer Purchase Decisions at Blibli Online Shopping Site (Study on NCT 127 fans in Bandar Lampung) - Salsabila Inggrid Widya Septi; Satria Bangsawan (International Journal of Regional Innovation, 2023)
Technological developments in Indonesia are currently growing rapidly and the presence of the internet has brought various conveniences and business opportunities for many people. The presence of the internet has enabled buying and selling activities to be carried out online, followed by the emergence of various online shopping or e-commerce sites in Indonesia, one of which is Blibli. Competition between e-commerce in Indonesia is getting tighter and the strategy used by Blibli in promoting their online shopping site is by taking advantage of the phenomenon that is currently being discussed, namely the Korean Wave phenomenon. Blibli takes advantage of this phenomenon by using K-Pop celebrity brand ambassadors as advertising stars and also building brand trust with consumers. NCT 127, a South Korean boy group with high popularity in Indonesia, was appointed as Blibli's brand ambassador. This study aims to determine the influence of NCT 127 as brand ambassadors and brand trust on consumer purchasing decisions on the online shopping site Blibli. The object of this research is NCT 127 fans in Bandar Lampung. This type of research is a quantitative research. This study used a purposive sampling method with a sample of 160 respondents and distributed via GoogleForm. This study uses multiple linear regression analysis and partial hypothesis testing (t-test). The results of the study show that partially there is a positive and significant influence between brand ambassador and brand trust variables on consumer purchasing decisions. The results obtained show that brand ambassadors have a positive and significant effect on consumer purchasing decisions with the highest contribution to the power dimension, and brand trust has a positive and significant effect on consumer purchasing decisions with the highest contribution to the trust dimension.